Characterization of MgO-based tundish working lining materials, microstructure and properties - Musmeci, Maximiliano Omar (2014)
A set of commercial tundish working lining materials was evaluated through a series of lab tests in order to determine the thermal evolution of both microstructure and mechanical properties, and their relationship with service conditions. Samples of each material were first casted with different water contents, then dried and fired at high temperatures. Microstructural characterization of these samples included density, porosity, pore size distribution determination and SEM observation. Particle size distribution, mineralogical (XRD) and chemical composition were also obtained. Thermogravimetric analysis was performed. Mechanical compressive strength for both green and fired (1600 °C) samples was also determined, as well as HMOR and dynamic elastic modulus of fired samples. Thermal shock resistance was evaluated by means of the mechanical characterization of sintered samples quenched in water. One of the failure mechanisms, rapid drying, was also studied. The impact of drying speed was evaluated by studying changes in the final compression resistance of sintered materials (1600 °C) obtained from materials previously submitted to different drying cycles with a gradual increase in the severity. Results showed good correlations between final properties, textural and microstructural features and materials processing conditions. Among them, water content was found to be a critical parameter that affects not only green samples porosity and mechanical strength, but also determines final mechanical properties after firing and sintering.